Pauses and Repetition on Students' Proposal Presentation - Yusuf, Israwati; Pakaya, Usman; Bay, Indri Wirahmi (Universitas Negeri Gorontalo, 2022)
Difficulties in delivering and understanding presentations can be due to several factors, especially in the psycholinguistics aspect, and due to errors. This research aimed to investigate the types of pauses and repetition and to describe the factors affecting pauses and repetition produced by English Department students during their proposal presentations. It uses a qualitative descriptive design by applying Dardjowidjojo theories. This research was completed with two data collection instruments: audio-visual material and structured interviews. The types of pauses and repetition obtained by audio-visual material and the factors affecting the pauses and repetition gained by structured interviews. By random purposive sampling, five (5) students were selected as the participants of this research. Some aspects are found in this research the first is Pauses which are divided into silent expiration, silent respiration, fillers, and discourse markers. The second is repetition, divided into repetition of words and sentences. The data analysis showed that psychological constraints, word choice, language interference, and limited English proficiency are the factor affecting pauses and repetition. Briefly, pauses and repetitions were made by all the participants during their proposal presentation.